2008
DOI: 10.1111/j.1600-0625.2007.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Polypodium leucotomos extract inhibits glutathione oxidation and prevents Langerhans cell depletion induced by UVB/UVA radiation in a hairless rat model

Abstract: In this report, we have addressed the effect of oral administration of a hydrophilic extract of the fern Polypodium leucotomos (PL) on the deleterious effects of ultraviolet radiation (UVR) on the levels of epidermal and plasmatic antioxidants in hairless rats. We have found that pretreatment with PL effectively reduced glutathione oxidation in both blood and epidermis, suggesting a potent systemic antioxidant effect. In addition, PL inhibited UVR-mediated Langerhans cell (LC) depletion. Our results demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 26 publications
2
40
0
2
Order By: Relevance
“…They also found a significant decrease in erythrocyte CAT activity. 35) Another study found a rise in activities of GST, GPX and CAT in hairless rat erythrocytes after acute UVB irradiation but the doses used (1540-2410 mJ/cm 2 ) were quite high. 36) Only one paper showed the effects of UVA light on erythrocyte antioxidant parameters in vivo, but the changes related to repeated UVA exposure.…”
Section: Discussionmentioning
confidence: 98%
“…They also found a significant decrease in erythrocyte CAT activity. 35) Another study found a rise in activities of GST, GPX and CAT in hairless rat erythrocytes after acute UVB irradiation but the doses used (1540-2410 mJ/cm 2 ) were quite high. 36) Only one paper showed the effects of UVA light on erythrocyte antioxidant parameters in vivo, but the changes related to repeated UVA exposure.…”
Section: Discussionmentioning
confidence: 98%
“…79 It has also been shown to reduce glutathione oxidation in the blood and epidermis following UVR exposure. 79 The associated reductions in pigmentation following oral use were presumed to reflect reduction in DNA damage through quenching of ROS, which would have otherwise facilitated melanogenesis. 80,81 Following UVA and UVB irradiation, PLE has been shown to reduce oxidative stress, inflammation, and DNA damage.…”
Section: Polypodium Leucotomos Extract (Ple)mentioning
confidence: 99%
“…PL prevents the elimination of Langerhans cells induced by UV irradiation during direct UV exposure [35], or PUVA-therapy [28]. It also inhibits the isomerization of trans -urocanic acid into the cis form and prevents further photo-induced breakdown and degradation in a cell-free system [34].…”
Section: Fernblock: a Multi-pronged Approach To Photoprotectionmentioning
confidence: 99%
“…It also inhibits the isomerization of trans -urocanic acid into the cis form and prevents further photo-induced breakdown and degradation in a cell-free system [34]. Finally, analysis of the blood and skin of mice treated orally with PL and subsequently irradiated with UV revealed that PL decreased the levels of oxidized glutathione and increased the activity of the enzyme catalase, suggesting a positive systemic effect in the antioxidant systems, particularly in skin [35]. …”
Section: Fernblock: a Multi-pronged Approach To Photoprotectionmentioning
confidence: 99%